Is new emission legislation stimulating the implementation of sustainable and energy-efficient maritime technologies?. (December 2015) - Stevens, Laurence; Sys, Christa; Vanelslander, Thierry; van Hassel, Edwin
Abstract: There is a significant increase in the attention given to green maritime ship technologies due to the growing importance of sustainable operations. The driving force behind this development is the implementation of several new legislative actions taken by the International Maritime Organization (IMO) and the European Union (EU). One of the main questions that arise is whether this new emission legislation stimulates the implementation of sustainable energy-efficient maritime technologies. In this paper, a framework is developed that allows linking the different emission legislation initiatives in different countries with the technical energy-efficient solutions that could be used to comply with the legislation. Based on this framework, the main research question can be answered. It turns out that the EEDI (Energy-Efficient Design Index) does not in the first place stimulate the introduction of new ship engine technologies nor the use of alternative fuels, but rather makes shipping companies order ships with a reduced design speed. SEEMP (Ship Energy Efficient Management Plan) on the contrary makes companies shift to bi-fuel engine systems, rather than fully to alternative energy systems. The findings are of relevance both to policy-makers and to shipping companies.